Influence of magnetic nanoparticles on the dielectric properties of Shell oil transformer oil - Kovalchuk, O.V.; Nesterenko, O.B.; Kotovskyi, V.Yo.; Studenyak, I.P.; Kovalchuk, T.M.; Paulovičová, K.; Timko, M.; Kopčanský, P.; Parekh, K.; Upadhyay, R.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2021)
The influence of two types of nano-impurities, MF1 and MF2, on the dielectric properties of Shell oil transformer oil at a temperature of 293 K has been studied. It has been shown that these magnetic impurities have no significant effect on the dielectric permittivity value of Shell oil, but more significantly increase its conductivity. In so doing, the impurity MF1 increases the conductivity of transformer oil by 4 times larger than the impurity MF2. It has been ascertained that the low-frequency dielectric relaxation appearing in the studied samples can be described by the Cole–Cole equation. The parameters of this relaxation process and the influence of different types of magnetic impurities on them have been estimated. Досліджено вплив двох типів нанодомішок MF1 та MF2 на діелектричні властивості трансформаторної олії Shell Oil при температурі 293 K. Показано, що такі магнітні домішки несуттєво впливають на величину діелектричної проникності Shell oil, проте більш суттєво збільшують її провідність, причому домішка MF1 збільшує провідність трансформаторної олії у 4 рази більше, ніж домішка MF2. Встановлено, що низькочастотну діелектричну релаксацію, яка виникає у досліджуваних зразках, можна описати рівнянням Коул–Коула. Оцінено параметри такого релаксаційного процесу і вплив на них різного типу магнітних домішок.